Group Activity Therapy Using Plant Plant Methods For The Elderly At Nursing Home - Ranal, Acep; Husniyah, Husniyah; Fienti, Yulia; Putri, Sindi Andika; Lenin, Farinas; Musrika, Musrika; Diana, Dewi; Xin, Derr (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The gerontological nursing stage is one part of the clinical practice of the nursing profession that must be completed by students. As a form of achieving learning goals, we carry out group activity therapy activities for the elderly using the method of planting plants in pots. Some of the health problems experienced by the elderly include hypertension, sensory disturbances, tremors, diabetes mellitus, and dementia. This activity aims to: increase creativity, patience, thoroughness, memory and fill spare time. Population: out of 15 elderly people at the Budi Social Batam Foundation for the Elderly, as many as 10 can take part in the skill of planting in pots. Students use the method; pre and post conference, namely before carrying out activities, students measure the ability of the elderly to participate in activities, then intervention is carried out planting in pots. Results; this activity is liked by the elderly, the elderly are very enthusiastic, but the elderly force themselves to lift the pots and planting media. Purpose. This activity aims to: increase creativity, patience, thoroughness, memory and fill spare time. Method. Pre and post conference, namely before carrying out activities, students measure the ability of the elderly to participate in activities, then intervention is carried out planting in pots. Results. This activity is liked by the elderly, the elderly are very enthusiastic, but the elderly force themselves to lift the pots and planting media. Conclusion. There is a significant difference regarding the ability to apply therapy activities between the pre-test and post-test, this shows that there is an ability and an increase in the elderly in filling out activities, one of which is skills.